Effect of Palm Oil Supplementation on the Milk Yield and Composition of Dromedary She Camels - Al-Dobaib, Soliman N. (Pakistan Journal of Nutrition, 2009)
Three diets were formulated according to percentage of palm oil added (C, control 0%; D1, 1.5%; D2, 3%) and offered to nine adult milking she camels. Camels were randomly allotted into three diets (3 animals each) and each diet shifted in three periods. Each period was splitted into 2 weeks for acclimatization and 2 weeks for data collection. Camels were machine milked twice a day (morning and afternoon). Animals were individually fed since feed and water were offered as free choice. Daily feed intake, milk yield and milk chemical composition were recorded. Obtained results showed significant effect of diets on daily feed consumption and daily milk yield. Adding palm oil in the diet resulted in a significant decrease in feed consumption (8.79, 7.94 and 7.05 kg/day for C, D1 and D2, respectively). Likewise, daily milk yield decreased significantly in treated females (2.89, 2.79, 2.46 kg/day for C, D1 and D2, respectively). Supplementing diets with palm oil at 1.5 and 3% didn’t affect milk composition (total solids, moisture, solid not fat, ash, fat, protein and lactose). Although, slight, but not significant increases in percent of milk fat (2.82, 3.02 and 3.01% for C, D1 and D2 respectively) were obtained, animals exhibited significant individual variations in milk composition. Addition of palm oil didn’t significantly influence milk calcium, sodium, potassium, phosphorus, magnesium, ferrous, manganese, zinc and sulphur. However, copper increased at D2 diet (4.76 ppm) than at control and D1 (3.04 and 3.31 ppm, respectively). It can be concluded that supplementing diets of milking she-camels with palm oil at the tested levels in this study caused a reduction in feed intake and milk yield but did not affect their milk composition except for a significant increase in the concentration of copper in camels that received 3% palm oil.